Desymmetrization as a Strategy in Asymmetric Halocyclization Reactions - Hennecke, Ulrich; Wilking, Michael (Synlett, 2014)
Halocyclization reactions such as halolactonization are powerful synthetic methods for the functionalization of alkenes and alkynes. However, asymmetric versions were thought of as difficult reactions and only recently have new asymmetric, organocatalytic halocyclization methods been reported. Herein, we examine a specific strategy for asymmetric halocyclization reactions, desymmetrizing cyclizations, and highlight recent contributions in this area.
Keywords: alkenes; asymmetric synthesis; cyclization; electrophilic addition; halogenation